2013
DOI: 10.1255/jnirs.1042
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Wheat Yield and Protein Using Remote Sensors on Plots—Part I: Assessing near Infrared Model Robustness for Year and Site Variations

Abstract: Validation of reflectance-based prediction models for plant properties is often performed on just one or two years of data. Hence, we aimed to perform a more comprehensive study regarding the validation of prediction models for grain yield and protein concentration. A FieldSpec3 portable field spectroradiometer was used to measure canopy reflectance in spring wheat. Spectral reflectance data were collected from three different experimental locations in up to four different years during the period 2007-2010, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Importantly, the p-value was highly significant between number of identifications per category for all categories (p < 0.05), indicating that the slopes are highly associated with CP, NDF and MEC contents and their association is not due to random variation. Overgaard et al [57] showed that one or two years of spectral measurement are insufficient to build fully operational models for cereal property predictions. In this regard, our study employed 10 years (2002-2011) of observations, and should thus adequately represent the expected range of conditions in our study area.…”
Section: Spectral Slope Analysesmentioning
confidence: 99%
“…Importantly, the p-value was highly significant between number of identifications per category for all categories (p < 0.05), indicating that the slopes are highly associated with CP, NDF and MEC contents and their association is not due to random variation. Overgaard et al [57] showed that one or two years of spectral measurement are insufficient to build fully operational models for cereal property predictions. In this regard, our study employed 10 years (2002-2011) of observations, and should thus adequately represent the expected range of conditions in our study area.…”
Section: Spectral Slope Analysesmentioning
confidence: 99%
“…There are promising methods for in-season prediction of wheat (Triticum aestivum L.) yield, based on proximal crop canopy (multi-or hyperspectral) reflectance sensors (e.g. Solie et al 2012, Øvergaard et al 2013, Engström and Piikki 2016, Montesinos-López et al 2017, proximal crop canopy fluorescence sensors (Zecha et al 2017) and satellite-borne hyperspectral imaging (Wang et al 2014). Previous work has indicated that predictions made at later growth stages are generally more accurate than earlier predictions and that hyperspectral measurements are generally more accurate than predictions based on vegetation indices calculated from a few wavelength bands.…”
Section: Yield Predictions For In-season Eonr Predictionsmentioning
confidence: 99%
“…The information content of hyperspectral data for vegetation has much potential for mapping the biophysical properties of both agricultural and natural vegetation. 6,8,[21][22][23][24]…”
Section: Introductionmentioning
confidence: 99%